Teacher nursing and the competences development: reflections on Philippe Perrenoud's Theory - Saionara Nunes de Oliveira; Mariely Carmelina Bernardi; Marta Lenise do Prado; Daniele Delacanal Lazzari; Murielk Motta Lino; Maria do Carmo Vicensi (Universidade Federal de Santa Maria, 2015)
Aim: to reflect about the ten competencies necessary to the teacher, proposed by Perrenoud, from the perspective of higher education in nursing. Method: theoretical reflection. Results: in nursing education, considering the National Curriculum Guidelines established for over a decade, it is emphasized the need to develop skills and competencies in numerous orders. However, the need of teachers to build knowledge and foster reflection, appropriating themselves of possibilities offered by the notion of competence, in this scenario, remains. Conclusion: it is reflected that the ten competencies presented by Philippe Perrenoud offer possibilities that allow teachers to rethink and redirect their practices, adapting or offering new educational possibilities as situation or learning space